Disease Activity in Mitral Annular Calcification: A Multimodality Study. (February 2019) - Massera, Daniele; Trivieri, Maria G.; Andrews, Jack P.M.; Sartori, Samantha; Abgral, Ronan; Chapman, Andrew R.; Jenkins, William S.A.; Vesey, Alex T.; Doris, Mhairi K.; Pawade, Tania A.; Zheng, Kang H.; Kizer, Jorge R.; et al.
Abstract : Background: Mitral annular calcification (MAC) is associated with cardiovascular events and mitral valve dysfunction. However, the underlying pathophysiology remains incompletely understood. In this prospective longitudinal study, we used a multimodality approach including positron emission tomography, computed tomography, and echocardiography to investigate the pathophysiology of MAC and assess factors associated with disease activity and progression. Methods: A total of 104 patients (age 72±8 years, 30% women) with calcific aortic valve disease, therefore predisposed to MAC, underwent 18 F-sodium fluoride (calcification activity) and 18 F-Fluorodeoxyglucose (inflammation activity) positron emission tomography, computed tomography calcium scoring, and echocardiography. Sixty patients underwent repeat computed tomography and echocardiography after 2 years. Results: MAC (mitral annular calcium score >0) was present in 35 (33.7%) patients who had increased 18 F-fluoride (tissue-to-background ratio, 2.32 [95% CI, 1.81–3.27] versus 1.30 [1.22–1.49]; P <0.001) and 18 F-Fluorodeoxyglucose activity (tissue-to-background ratio, 1.44 [1.37–1.58] versus 1.17 [1.12–1.24]; P <0.001) compared with patients without MAC. MAC activity ( 18 F-fluoride uptake) was closely associated with the local calcium score and 18 F-Fluorodeoxyglucose uptake, as well as female sex and renal function. Similarly, MAC progression was closely associated with local factors, in particular, baseline MAC. Traditional cardiovascular risk factors and calcification activity in bone or remote atherosclerotic areas were not associated with disease activity nor progression. Conclusions: MAC is characterized by increased local calcification activity and inflammation. Baseline MAC burden was associated with disease activity and the rate of subsequent progression. This suggests a self-perpetuating cycle of calcification and inflammation that may be the target of future therapeutic interventions. Abstract : Supplemental Digital Content is available in the text.